Height Effect on Interactions between the Hydraulic Fracture and Natural Fractures. (17th October 2022) - Wang, Daobing; Taleghani, Arash Dahi; Yu, Bo
Abstract : Since natural fractures have shorter heights, it is necessary to incorporate the height difference in the mechanical behavior of hydraulic fracture crossing cemented natural fractures at different angles. However, the impact of fracture height growth on the mechanical behavior of intersection of natural fracture and hydraulic fracture is not yet fully understood at present. In this study, we use adaptive cohesive zone methods to investigate the impact of fracture height on the mechanical behaviors of a propagating hydrofracture crossing natural fractures at different intersection angles. The fracture patterns and mechanical mechanisms for crack propagation crossing with cemented natural fractures are discussed. The increase of fracture height could restrain the crack propagation along the southwest orientation of the natural fracture, but it hardly affects the propagation along the northeast orientation of the natural fracture. A lot of bands appear at a relatively larger formation thickness. The stress shadow between adjacent cohesive layers increases as the formation height increases, which could promote crack initiation and propagation between the adjacent joints or natural fractures. The cracking zone is related to the position of the natural fracture or joint sets with respect to the advancing hydrofracture. Key factors, including the formation height, tensile strength of cemented natural fractures, and their intersection angle with the growing hydrofracture propagation, are investigated in details. In addition, the pressure fluctuation frequency increases as the fracture height increases due to the strong hydraulic and natural fracture interaction. This study provides a new perspective for the development of complex fracture network patterns in cemented formations.